Malcolm X a life of reinvention - Marable, Manning 1950-2011 (New York penguine Goup, 2011)
This biography of Malcolm X draws on new research to trace his life from his troubled youth through his involvement in the Nation of Islam, his activism in the world of Black Nationalism, and his assassination. Years in the making, it is a definitive biography of the legendary black activist. Of the great figures in twentieth-century American history perhaps none is more complex and controversial than Malcolm X. Constantly rewriting his own story, he became a criminal, a minister, a leader, and an icon, all before being felled by assassins' bullets at age thirty-nine. Through his tireless work and countless speeches he empowered hundreds of thousands of black Americans to create better lives and stronger communities while establishing the template for the self-actualized, independent African American man. In death he became a broad symbol of both resistance and reconciliation for millions around the world. Filled with new information and shocking revelations that go beyond the Autobiography of Malcolm X, this work unfolds a story of race and class in America, from the rise of Marcus Garvey and the Ku Klux Klan to the struggles of the civil rights movement in the fifties and sixties. Reaching into Malcolm's troubled youth, it traces a path from his parents' activism through his own engagement with the Nation of Islam, charting his astronomical rise in the world of Black Nationalism and culminating in the never-before-told true story of his assassination. This work captures the story of one of the most singular forces for social change, a man who constantly strove, in the great American tradition, to remake himself anew
Life beyond the legend -- "Up, you mighty race" : 1925-1941 -- The legend of Detroit Red : 1941-January 1946 -- Becoming "X" : January 1946-August 1952 -- "They don't come like the minister" : August 1952-May 1957 -- "Brother, a minister has to be married" : May 1957-March 1959 -- "The hate that hate produced" : March 1959-January 1961 -- "As sure as God made green apples" : January 1961-May 1962 -- From prayer to protest : May 1962-March 1963 -- "He was developing too fast" : April-November 1963 -- "The chickens coming home to roost" : December 1, 1963-March 12, 1964 -- An epiphany in the Hajj : March 12-May 21, 1964 -- "Do something about Malcolm X" : May 21-July 11, 1964 -- "In the struggle for dignity" : July 11-November 24, 1964 -- "Such a man is worthy of death" : November 24, 1964-February 14, 1965 -- Death comes on time : February 14-February 21, 1965 -- Life after death -- Reflections on a revolutionary vision
Includes bibliographical references (p. 563-576) and index
1
Keywords: X, Malcolm -- 1925-1965; African American Muslims -- Biography; African American civil rights workers -- Biography; African Americans -- Biography; Black Muslims -- Biography; Black nationalism -- United States